Development of Electronic Book (E-Book) EPUB-Based for Display Course - Oktafiany Widhi Astuti; Djoko Dwi Kusumajanto (JPBM (Jurnal Pendidikan Bisnis dan Manajemen), 2017)
The aim of this research is to produce a source of learning in the form of electronic book (e-book) with EPUB format for the Product Management Subject, and measuring the effectiveness of the use of e-book as a source for student learning independently. The study was conducted using the development model proposed by Sugiyono. This study used a questionnaire to obtain data validated by an expert. Students are as audience in learning using e-book based EPUB. The average of validation result and trial of effectiveness of EPUB-based e-book used calculation of joint validity which resulted percentage of 86,14% which means very valid and suitable to be used as alternative learning source for the Product Management Subject.